THE INFLUENCE OF THE MARKETING MIX ON DECISIONS PROSPECTIVE STUDENTS CHOOSE HIGHER EDUCATION AT BANYUWANGI MARINE ACADEMY - Fandi Ahmad; Muhammad Firdaus; Agustin HP (Jurnal Ekonomi, 2023)
This study aims to determine the effect of the Product, Price, Promotion and Place marketing mix simultaneously or partially for each variable on the decision of prospective students to continue their education at the Banyuwangi Maritime Academy. A quantitative research method with a saturated sample system was used in a study of 62 respondents in the registration for the first wave of the 2022/2023 academic year, the research results obtained were processed with the help of the SPSS program. Based on the results of the F test, it is known that Product, Price, Promotion and Place simultaneously have an effect significant to the Choice Decision , referring to the value of the Coefficient of Determination ( ) which is 0.359 which means that there is an influence of 35.9% while 64.1% of the decision to choose by prospective students is influenced by other variables not examined in this study. Partially, Product has a partially significant effect on the decision to choose. Price has no significant effect partially on the Choosing Decision. Variable Promotion also has no significant effect partially on the decision to choose. Variable Place has no significant effect partially on the decision to choose.